Effectiveness of clean intermittent self catheterization in patients with recurrent urethral stricture post visual internal urethrotomy - Naqib Ullah; Jamshid Nawaz; Muhammad Shoaib; Asif Khan; Nizam ud Din; Tauheed Fareed (Journal of Rawalpindi Medical College)
OBJECTIVE :